A parity-time-symmetric optoelectronic oscillator with polarization multiplexed channels. (1st May 2022) - Özgün, Ege; Uyar, Faruk; Kartaloglu, Tolga; Ozbay, Ekmel; Ozdur, Ibrahim
Abstract: In this manuscript, we experimentally demonstrate a parity-time-symmetric optoelectronic oscillator (OEO) with polarization multiplexed channels. We obtained a microwave single-mode oscillation at 9.5 GHz with phase noise values of −116.2 and −122.3 dBc Hz −1 at 10 kHz offset frequencies, and side mode suppression values below −68 and −75 dBc Hz −1, by utilizing a 1 km long and 5 km long single mode fiber delay lines, respectively. Our experimental results suggest that parity-time-symmetric OEOs with polarization multiplexed channels are simple and cost-efficient alternatives to their more complex counterparts.